Internet of Things-based fire alarm monitoring system for industrial electrical panels - M Fauzi, Zikri Kurnia; Ranuharja, Fadhli; Mukhaiyar, Riki; Hastuti (Department of Electrical Engineering Universitas Negeri Padang, 2025)
Industrial electrical panels play a crucial role in electrical systems, particularly in power distribution and electric machine control panels that operate continuously during production processes. However, they also pose a potential fire hazard due to factors such as human error or equipment malfunction, including high temperatures, gas leaks, or undetectable installation errors. This study aims to design a fire alarm monitoring system based on the Internet of Things using an ESP32 microcontroller integrated with a DHT22 temperature and humidity sensor, an MQ-2 gas sensor, and a flame sensor. The research adopts an experimental method. A three-phase distribution panel is used in this study. Based on the test results, sensor data can be displayed in real time through an LCD and the Blynk application, and automatically logged to Google Sheets. The results demonstrate that the system is capable of detecting hazardous conditions and providing early warning alerts via an alarm